Effects of Shen Men Auricular Acupressure on Haemodynamics During Laryngoscopy and Intubation and Preoperative Anxiety - Boon, Kah Yoong; Mohamad Mahdi, Siti Nidzwani; Mohtar Rasali, Emilia; Wan Mat, Wan Rahiza; Tang, Shereen Suet Ping (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Laryngoscopy and endotracheal intubation is known to cause tachycardia and increase in blood pressure during general anaesthesia. This study was designed to assess if auricular acupressure has beneficial effects in attenuating the haemodynamic changes during laryngoscopy and intubation. Secondly, this study aimed to evaluate the effectiveness of auricular acupressure in reducing preoperative anxiety. MATERIALS AND METHODS: Eighty patients who were scheduled for surgery under general anaesthesia were randomised to receive either active auricular acupressure over bilateral Shen Men (Group A) or sham auricular acupressure (Group B). A total of three stimulations of auricular acupressure with ten minutes interval were performed before induction of anaesthesia. Haemodynamic parameters (heart rate and blood pressure) were recorded ten minutes after each stimulation, during laryngoscopy and intubation and every minute for ten minutes after intubation. Visual analogue scale for anxiety was documented before and at 30 minutes post first stimulation. RESULTS: The heart rate and mean arterial pressure were statistically higher in Group B comparing to Group A during intubation (p=0.043 and p=0.049 respectively). There was statistically significant reduction in blood pressure after intubation in both groups as compared to baseline (p<0.003 respectively). However, there was no significant difference when comparing both groups (p>0.05). There was no significant reduction of preoperative anxiety level in both groups after auricular acupressure (p=0.879). CONCLUSION: Auricular acupressure over bilateral Shen Men helped to attenuate the haemodynamic changes during intubation. However, it did not reduce preoperative anxiety.